Sobre Karen Racine y Graham Lloyd (eds.), The Journal of James A. Brush. The Expedition and Military Operations of General Don Francisco Xavier Mina in Mexico, 1816-1817 - Díaz Barrera, Jorge Alejandro (El Colegio de México, A.C., 2023)
-